Gay Hotsa ; ondertitel vanaf (1986) 33 : revista gai de informacion y cultura. (Bilbo : EHGAM, 1977)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Esk. Solokoetxe 4, 48080 Bilbo
Spaans
Periodiek